Nurses’ practical contributions to improving healthy and sustainable public spaces: an integrative review - Herlys Rafael Pereira do Nascimento; Ingrid Mikaela Moreira de Oliveira; Grayce Alencar Albuquerque; Edilma Gomes Rocha Cavalcante; Marlene Menezes de Souza Teixeira; Maria do Socorro Vieira Lopes (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to identify knowledge production about nurses’ contributions to improving healthy and sustainable public spaces. Methods: an integrative review carried out in February 2023 in electronic databases. Studies that answered the research question and that were available in full, in Portuguese, English and Spanish, were included. Results: a total of five articles were selected. The findings highlighted the importance of educational projects in the training of local managers and community autonomy; citizen participation and health promotion as ways to implement Sustainable Development Goal 11; nurses as facilitators of collective care; new health practices and modes of producing subjectivity; and use of public transportation, bicycles and/or walking in these spaces. Final considerations: there is a clear need for greater incentives from local governments to develop effective sustainability strategies that are led by nurses and the community.